Selective serotonin reuptake inhibitors versus placebo in patients with major depressive disorder A systematic review with meta-analysis and Trial Sequential Analysis - Jakobsen, Janus Christian; Katakam, Kiran Kumar; Schou, Anne; Hellmuth, Signe Gade; Stallknecht, Sandra Elkjær; Leth-Møller, Katja; Iversen, Maria; Banke, Marianne Bjørnø; Petersen, Iggiannguaq Juhl; Klingenberg, Sarah Louise; Krogh, Jesper; Ebert, Sebastian Elgaard; et al. (BMC Psychiatry, 2017)
[Correction Notice: An Erratum for this article was reported in Vol 17[162] of BMC Psychiatry (see record [rid]2017-20306-001[/rid]). In the original article, there are some textual errors in the Results section and in Table 2. Corrections are provided in the erratum.] Background: The evidence on selective serotonin reuptake inhibitors (SSRIs) for major depressive disorder is unclear. Methods: Our objective was to conduct a systematic review assessing the effects of SSRIs versus placebo, ‘active’ placebo, or no intervention in adult participants with major depressive disorder. We searched for eligible randomised clinical trials in The Cochrane Library’s CENTRAL, PubMed, EMBASE, PsycLIT, PsycINFO, Science Citation Index Expanded, clinical trial registers of Europe and USA, websites of pharmaceutical companies, the U.S. Food and Drug Administration (FDA), and the European Medicines Agency until January 2016. All data were extracted by at least two independent investigators. We used Cochrane systematic review methodology, Trial Sequential Analysis, and calculation of Bayes factor. An eight-step procedure was followed to assess if thresholds for statistical and clinical significance were crossed. Primary outcomes were reduction of depressive symptoms, remission, and adverse events. Secondary outcomes were suicides, suicide attempts, suicide ideation, and quality of life. Results: A total of 131 randomised placebo-controlled trials enrolling a total of 27,422 participants were included. None of the trials used ‘active’ placebo or no intervention as control intervention. All trials had high risk of bias. SSRIs significantly reduced the Hamilton Depression Rating Scale (HDRS) at end of treatment (mean difference −1.94 HDRS points; 95% CI −2.50 to −1.37; P < 0.00001; 49 trials; Trial Sequential Analysis-adjusted CI −2.70 to −1.18); Bayes factor below predefined threshold (2.0110−23). The effect estimate, however, was below our predefined threshold for clinical significance of 3 HDRS points. SSRIs significantly decreased the risk of no remission (RR 0.88; 95% CI 0.84 to 0.91; P < 0.00001; 34 trials; Trial Sequential Analysis adjusted CI 0.83 to 0.92); Bayes factor (1426.81) did not confirm the effect). SSRIs significantly increased the risks of serious adverse events (OR 1.37; 95% CI 1.08 to 1.75; P = 0.009; 44 trials; Trial Sequential Analysis-adjusted CI 1.03 to 1.89). This corresponds to 31/1000 SSRI participants will experience a serious adverse event compared with 22/1000 control participants. SSRIs also significantly increased the number of non-serious adverse events. There were almost no data on suicidal behaviour, quality of life, and long-term effects. Conclusions: SSRIs might have statistically significant effects on depressive symptoms, but all trials were at high risk of bias and the clinical significance seems questionable. SSRIs significantly increase the risk of both serious and non-serious adverse events. The potential small beneficial effects seem to be outweighed by harmful effects. (PsycInfo Database Record (c) 2020 APA, all rights reserved)
Keywords: Depression; Major Depression; Placebo; SSRI; Serotonin Reuptake Inhibitors; Systematic review